Odpowiedzi

2010-02-06T12:27:42+01:00
-6(x+1)=24 : (-6)
x + 1 = -4 -1
x = -5

-7(x-2)=3x-1
-7x + 14 = 3x - 1
-7x - 3x = -1 - 14
-10x = -15
x = 1,5

4(x-1)=6(1+x)
4x - 4 = 6 + 6x
4x - 6x = 6 + 4
-2x = 10
x = (-5)
2010-02-06T12:28:38+01:00
A)
-6(x+1)=24/:-6
x+1 = -4
x= -5
B)
-7(x-2)=3x-1
-7x + 14 =3x - 1
15 = 10x
x = 1,5
c)
4(x-1)=6(1+x)
4x - 4 = 6 +6x
-2x = 10
x=-5
Najlepsza Odpowiedź!
2010-02-06T12:29:28+01:00
A)-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 /:(-6)
x=-5
b) -7(x-2=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15 /: (-10)
x=1,5
c) 4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10 /:(-2)
x=-5